The Achievement of Flourishing in the Elderly through Education at Pesantren - Dinie Ratri Desiningrum; Yeniar Indriana; Suparno Suparno; Tazkiyah Aulia (Gadjah Mada Journal of Psychology (GamaJoP), 2023)
This study aims to explore the flourishing in elders. In this study, the authors carried out a mixed method, a quantitative method in the form of giving two questionnaires, namely independence and resilience which were analyzed descriptively from each variable, and qualitative methods by developing an in-depth interview based on Seligman’s concept of flourishing. The interview had open questions, which were given to eight santri as research subjects aged 55 to 76 years. Data were analyzed using qualitative methods, i.e., Interpretative Phenomenology Analysis (IPA) techniques. The results of the study showed that the elderly have fairly good flourishing achievements. They can do daily activities naturally formed from the results of habituation while in pesantren. They also have high independence and resilience as has been revealed in previous research which used quantitative methods that showed a high level of both variables. It can be concluded that the activities can increase the independence and resilience of the elderly who become santri and with habituation carried out can bring the elderly to achieve flourishing.